Retiros extraordinarios: estimación de los requerimientos de liquidez de las entidades bancarias - Mejía , Kléber (2005)
This research constitutes a methodological proposal to estimate the additional liquidity requirements (ALR) of a financial institution when its deposit withdrawals exceed the minimum levels of its monetary stock, defined by the holdings of national and foreign accounts, and stocks. By means of multivariate non-parametric simulation procedures we generated various scenarios of financial stress, 1.e. events where the amount of deposit withdrawals exceeded the liquid assetholdings of the institutions. These cases were quantified in order to build the probability distribution for the occurrence of financial stress events, allowing us to calculate the liquidity gaps. The model built considered the historical weekly behavior of the total deposits as well as of the liquid assets of each bank in the system between May 27, 1997 and September 15, 2004